Military Service and Decision Quality in the Management of Knee Osteoarthritis. Issue 7 (28th June 2018) - Henderson, Eric R; Titus, Alexander J; Keeney, Benjamin J; Goodney, Philip P; Lurie, Jon D; Ibrahim, Said A
Abstract: Background: Decision quality measures the degree to which care decisions are knowledge-based and value-aligned. Because military service emphasizes hierarchy, command, and mandates some healthcare decisions, military service may attenuate patient autonomy in healthcare decisions and lower decision quality. VA is the nation's largest provider of orthopedic care. We compared decision quality in a sample of VA and non-VA patients seeking care for knee osteoarthritis. Methods: Our study sample consisted of patients newly referred to our orthopedic clinic for the management of knee osteoarthritis. None of the study patients were exposed to a knee osteoarthritis decision aid. Consenting patients were administered the Hip/Knee Decision Quality Instrument (HK-DQI). In addition, they were surveyed about decision-making preferences and demographics. We compared results to a non-VA cohort from our academic institution's arthroplasty database. Results: The HK-DQI Knowledge Score was lower in the VA cohort (45%, SD = 22, n = 25) compared with the non-VA cohort (53%, SD = 21, n = 177) ( p = 0.04). The Concordance Score was lower in the VA cohort (36%, SD = 49%) compared with the control cohort (70%, SD 46%) ( p = 0.003). Non-VA patients were more likely to make a high-quality decision ( p = 0.05). Non-VA patients were more likely to favor a shared decision-making process ( p = 0.002). Conclusions: Decision quality is lower in Veterans with knee osteoarthritis compared with civilians, placing them at risk for lower treatment satisfaction and possibly unwarranted surgical utilization. Our future work will examine if this difference is from conditioned military service behaviors or confounding demographic factors, and if conventional shared decision-making techniques will correct this deficiency.